2002
DOI: 10.1007/s00402-002-0423-6
|View full text |Cite
|
Sign up to set email alerts
|

Rationales of arthroscopic shoulder stabilization

Abstract: Arthroscopic reconstruction of glenohumeral instability has become more common during the past decade. Compared with open reconstruction, which is still the gold standard in the treatment of shoulder instability, arthroscopic techniques allow for improved diagnosis of numerous intraarticular findings. This review presents an appropriate system for the arthroscopic classification of most pathological findings in patients with anterior shoulder instability. Based on the presented classification, a rationale for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Standardised methods of stabilisation have been established using different types of anchors and sutures. In young patients, at high risk for repeated shoulder dislocation, early operative intervention is recommended [16]. Though promising results have been achieved it is still difficult to predict the individual patient's risk of redislocation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Standardised methods of stabilisation have been established using different types of anchors and sutures. In young patients, at high risk for repeated shoulder dislocation, early operative intervention is recommended [16]. Though promising results have been achieved it is still difficult to predict the individual patient's risk of redislocation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the open reconstruction technique, together with arthroscopic methods, is a sufficient method to treat posttraumatic, unidirectional shoulder instability [3,16]. It has been shown that the anterior capsulolabral reconstruction according to Jobe [12] enables a reliable restoration of shoulder stability together with a low rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Benefits of arthroscopic stabilization include limited disruption to the subscapularis, increased ability to address concomitant intra-articular shoulder pathology, improved postprocedural external rotation, minimized postoperative pain, and decreased morbidity. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introduction (With Video Illustration)mentioning
confidence: 99%
“…9,10 Benefits of arthroscopic stabilization include limited disruption to the subscapularis, increased ability to address concomitant intra-articular shoulder pathology, improved postprocedural external rotation, minimized postoperative pain, and decreased morbidity. [11][12][13][14][15][16][17][18] When considering arthroscopic stabilization, there are 2 main patient positioning options: "beach chair" and lateral decubitus. It is our preference to address shoulder instability in the lateral decubitus position when treating it arthroscopically.…”
Section: Introduction (With Video Illustration)mentioning
confidence: 99%